Mechanical and physical properties of sago starch/halloysite nanocomposite film - Ahmad, Zuraida; Hermain, Hazwan Yatimi; Abdul Razak, Nur Humairah (Trans Tech Publications Ltd., Switzerland, 2015)
The incorporation of unmodified halloysite nanotube (HNT) in a thermoplastic sago starch (TPSS) film to form a nanocomposite material was investigated. The TPSS/HNT nanocomposite was fabricated through solvent casting method at varying HNT loading of 0, 0.25, 0.5, 1.0, 3.0, and 5.0 wt.%. Evaluation on mechanical and physical properties (tensile test, water absorption, thickness and density) was made to study the effect of HNT loading on the TPSS properties. Tensile strength achieved an optimum value at 0.25 wt.% of HNT loading and decreased with higher addition of HNT. Meanwhile higher amount of HNT in the nanocomposite film exhibited brittleness with the reduced tensile strain. Water absorption decreased with the addition of HNT due to the difficulty of water molecules to pass through the tortuous path of HNT structure. Thickness and density of the nanocomposite film, however, increased at higher HNT contents. FESEM (field emission scanning electron microscope) which examined the surface morphology of the TPSS/HNT nanocomposite displayed uniformly dispersed HNT in the plasticized starch matrix.